An Overview of Empirical Studies on “Continuation Task” in China - Ziyi Wang (Journal of Linguistics and Communication Studies, 2024)
“Writing after reading” is a method proposed by Professor Chuming Wang for promoting foreign language learning and teaching. With the deepening of related researches, Professor Wang has recently promoted it as “Xu Theory”. In order to better understand the development and the present situation of the study of this method in China, through searching the theme “continuation task” and time range “2017-2023”, this paper has found that there are 46 papers published in Chinese key journals of foreign languages, including 37 empirical articles. Based on those papers, this paper makes a review of the “writing after reading” task during the past 7 years, from the perspectives of its theoretical background and its present research status, summarizes the existing problems in current research and puts forward some suggestions.